"Landschap". - Baeck, G.; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1987)
Ampe, Dominique ; Coorevits, Raf ; De Vuyst, Gaspard ; Frimout, Cyr ; Raveel, Roger ; Roelant, André ; Van den Dries, Maurice ; Van Den Driessche, Lucien ; Van Gysegem, Paul ; Vercoutere, Frans ; Vermoote, Anne-Marie
"Landschap", Hof ter Nederloo, Sint-Pieters-Leeuw, 16 januari - 15 februari 1987
boek